COACHING AND TRAINING SKILLS PARTICIPANTS OF PKH PROGRAM IN DEVELOPING POTTERY PRODUCTS AT TONDOWULAN VILLAGE, PLANDAAN, JOMBANG - Rahayu, Hartono (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
The purpose of coaching and training skills for low-economy families, especially those incorporated of the PKH Social Funds conducted by the social department of Jombang regency is to improve economic income and family welfare. This coaching and training skills attended by 25 participants that consists of recipient of PKH program form social ministry: 1) Woman family head, 2) Woman who has productive economic business. This training used some methods such as lectures, interview, practice producing pottery with designs. The expected outcomes: 1) The participants have demonstrated the desire to develop and manage the business with the intention to attract customers and increase the income of families and village societies, 2) participants who have a business to respond to know and apply the right marketing strategy for their business continuity, and 3) Participants got new knowledges to produce some pottery designs which currently in demand market